Pheromone-Induced Odor Associative Fear Learning in Rats. Issue 1 (December 2018) - Carew, Samantha; Mukherjee, Bandhan; MacIntyre, Iain; Ghosh, Abhinaba; Li, Sa; Kirouac, Gilbert; Harley, Carolyn; Yuan, Qi
Abstract Alarm pheromones alert conspecifics to the presence of danger. Can pheromone communication aid in learning specific cues? Such facilitation has an evident evolutionary advantage. We use two associative learning paradigms to test this hypothesis. The first is stressed cage mate-induced conditioning. One pair-housed adult rat received 4 pairings of terpinene + shock over 30 min. Ten minutes after return to the home cage, its companion rat was removed and exposed to terpinene. Single-housed controls were exposed to either terpinene or shock only. Companion rats showed terpinene-specific freezing, which was prevented by β-adrenoceptor blockade. UsingArc to index neuronal activation in response to terpinene re-exposure, stressed cage-mate induced associative learning was measured. Companion rats showed increased neuronal activity in the accessory olfactory bulb, while terpinene + shock-conditioned rats showed increased activity in the main olfactory bulb. Both groups had enhanced activity in the anterior basolateral amygdala and central amygdala. To test involvement of pheromone mediation, in the 2nd paradigm, we paired terpinene with soiled bedding from odor + shock rats or a rat alarm pheromone. Both conditioning increased rats' freezing to terpinene. Blocking NMDA receptors in the basolateral amygdala prevented odor-specific learning suggesting shock and pheromone-paired pathways converge in the amygdala. An alarm pheromone thus enables cue-specific learning as well as signalling danger.